A Busted Sac: A Case of Spontaneous Bladder Rupture Secondary to Acute Urinary Retention in a Healthy Middle-Aged Male - Maddie Perdoncin MSC; Ebubechukwu Ezeh MD; Onyinye Ugonabo MD; Roger Robertson MD; Christine Gilkerson MD (SAGE Publishing, 2023)
Spontaneous bladder rupture is a relatively rare medical emergency that can be easily misdiagnosed. Although spontaneous bladder rupture is more common in those with previously diagnosed bladder conditions, this phenomenon may also occur in patients with an otherwise insignificant past medical history. Early diagnosis and treatment are critical to avoid fatal complications. Here, we present a 49-year-old male with insignificant past medical history who was diagnosed with spontaneous bladder rupture after the attempted placement of a Foley catheter.